The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1073/pnas.82.5.1391
|View full text |Cite
|
Sign up to set email alerts
|

Recombination in mouse L cells between DNA introduced into cells and homologous chromosomal sequences.

Abstract: In this paper, we show that DNA added to mouse L cells by the calcium phosphate method can be inserted into the genome of those cells by homologous recombination. The insertion event is detected because it reconstructs a functional thymidine kinase (tk) gene from two defective genes that share 320 base pairs of homology. One of the genes is missing its 5' portion (tkA5') and is in the cell's chromosome, and the other is missing its 3' portion (tkA3') and is in the introduced DNA. 40 (6, 7, 9) indicates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(66 citation statements)
references
References 41 publications
1
62
0
1
Order By: Relevance
“…Since site-specific integration of genes appears to be extremely rare (8,16,17), it would be of interest to determine whether genetic mutations can be corrected by gene conversion from segments of DNA introduced artificially elsewhere into the genome. We are also exploring whether gene conversion can be used as a mechanism to exchange genetic information between replicating extrachromosomal molecules and the chromosomes of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since site-specific integration of genes appears to be extremely rare (8,16,17), it would be of interest to determine whether genetic mutations can be corrected by gene conversion from segments of DNA introduced artificially elsewhere into the genome. We are also exploring whether gene conversion can be used as a mechanism to exchange genetic information between replicating extrachromosomal molecules and the chromosomes of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this are not known, but the effect seems to exist. For example, separate studies were conducted by Lin et al [25] and Thomas et al [42] both involving gene targeting of artificially introduced defective genes in mouse fibroblasts. Lin et al reported a ratio of random integration to gene targeting of 100 000:1 whereas Thomas et al reported a ratio of 100:1.…”
Section: Transfection Methodsmentioning
confidence: 99%
“…In yeast, DSB repair occurs largely by homologous recombination (4)(5)(6)(7). Although capable of homologous recombination, higher eukaryotic species repair DSBs primarily by a process of nonhomologous or illegitimate recombination (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%